Transferable skills representations in a Portuguese college sample: gender, age, adaptability and vocational development - Rocha, Magda (2016)
The departing point of this study is the theoretical framework of “Making the Match project” (Evers and Rush in Management Learning 27:275–299, 1996) about how to develop a common language among stakeholders regarding transferable skills. Thus, the paper examines the impact of demographic variables (age and gender) and developmental dimensions (Career adaptability and Vocational development) in the representations of transferable skills construction within a Portuguese sample of first-year college students (Vocational developmental variables are part of career construction theory; Savickas 2001, 2002, 2005, Journal of Vocational Behavior 75:239–250, 2009), a theoretical framework that significantly supports the notion that the acquisition of transferable skills is one of the consequences of vocational tasks’ resolution. Results suggested that career adaptability seems to be the most robust predictor for the transferable skills’ groups advanced by Evers and colleagues, followed by career development, and, finally, age and gender as a block. Results are discussed in the light of the two aforementioned main frameworks.